Lost in Acculturation? Premigratory Exposure to Democracy and Immigrants' Political Trust in the United States. (14th February 2018) - Wals, Sergio C; Rudolph, Thomas J
Abstract: Using data from the 2003 Mexican Values Survey and an innovative approach to capture premigration socialization, this article analyzes the impact of political experience before migration and its interaction with acculturation in shaping Latino immigrants' attitudes toward government in the United States. Findings show that trust in government in the new host nation is shaped by individuals' premigratory exposure to democracy during preadult socialization in their countries of origin. Immigrants who were socialized under more democratic regimes exhibit less trust in the national government than do their counterparts socialized under authoritarian systems. We also find a negative effect of acculturation on trust in all levels of government, an effect that is moderated by both premigratory exposure to democracy and by income.